JAMIR-eQTL: Japanese genome-wide identification of microRNA expression quantitative trait loci across dementia types. (3rd November 2021) - Akiyama, Shintaro; Higaki, Sayuri; Ochiya, Takahiro; Ozaki, Kouichi; Niida, Shumpei; Shigemizu, Daichi
Abstract: MicroRNAs (miRNAs) are small non-coding RNAs shown to regulate gene expression by binding to complementary transcripts. Genetic variants, including single-nucleotide polymorphisms and short insertions/deletions, contribute to traits and diseases by influencing miRNA expression. However, the association between genetic variation and miRNA expression remains to be elucidated. Here, by using genotype data and miRNA expression data from 3448 Japanese serum samples, we developed a computational pipeline to systematically identify genome-wide miRNA expression quantitative trait loci (miR-eQTLs). Not only did we identify a total of 2487 cis -miR-eQTLs and 3 155 773 trans -miR-eQTLs at a false discovery rate of <0.05 in six dementia types (Alzheimer's disease, dementia with Lewy bodies, vascular dementia, frontotemporal lobar degeneration, normal-pressure hydrocephalus and mild cognitive impairment) and all samples, including those from patients with other types of dementia, but also we examined the commonality and specificity of miR-eQTLs among dementia types. To enable data searching and downloading of these cis - and trans -eQTLs, we developed a user-friendly database named JAMIR-eQTL, publicly available at https://www.jamir-eqtl.org/ . This is the first miR-eQTL database designed for dementia types. Our integrative and comprehensive resource will contribute to understanding the genetic basis of miRNA expression as well as to the discovery of deleterious mutations, particularly in dementia studies. Database URL : https://www.jamir-eqtl.org/